Case report: Near-fatal hypermagnesemia resulting from the use of Epsom salts in a patient with normal renal function - Si, Gui-Fei; Ge, Yu-Xin; Lv, Xiao-Pan; Li, Yu-Quan; Chen, Xue-Mei; Yuan, Xue-Min (Frontiers in Medicine, 2024)
Hypermagnesemia commonly occurs in patients with renal dysfunction. Diagnosing hypermagnesemia represents a challenge due to its rarity and the absence of routine monitoring of magnesium levels. Furthermore, the lack of awareness among clinicians regarding this uncommon condition frequently leads to delayed diagnoses. Few patients survive with a serum magnesium level exceeding 7 mmol/L. This article presents a case study of near-fatal hypermagnesemia resulting from the oral administration of Epsom salts in a patient with normal renal function. A 60-year-old female presented to the gastroenterology department on Oct. 6, 2023, with a 3-day history of black stools. She underwent subtotal gastrectomy in 2005 and has a stable history of nephrotic syndrome. To investigate the cause of her bleeding, electronic gastroscopy and colonoscopy were scheduled for Oct. 11, 2023. She experienced a sudden loss of consciousness 30 min after the ingestion of Epsom salts. The attending physician suspected a severe magnesium poisoning. She was promptly administered calcium gluconate, underwent tracheal intubation with ambu bag ventilation, and received early continuous renal replacement therapy (CRRT). Swift diagnosis and CRRT contributed to a reduction in her serum magnesium levels from an initial 8.71 mmol/L to 1.35 mmol/L, leading to a remarkable improvement in the toxic symptoms associated with hypermagnesemia. Subsequently, she was managed in the gastroenterology department, with gastroscopy revealing bleeding from the gastrointestinal anastomotic ulcer. Following conservative treatments including acid suppression, stomach protection, and hemostasis, her symptoms improved, and she was successfully discharged. This study aims to alert clinicians to the possibility of hypermagnesemia in individuals with normal renal function. Physicians should exercise caution when prescribing Epsom salts to patients with underlying gastrointestinal conditions. If necessary, alternative drug therapies may be considered to mitigate the risk of hypermagnesemia. Timely intervention is pivotal in averting life-threatening complications linked to hypermagnesemia.